2018
DOI: 10.1159/000491890
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of Long Noncoding RNAs in Primary Immune Thrombocytopenia: A Microarray Related Study

Abstract: Background/Aims: Long noncoding RNAs (lncRNAs) are important regulators of biological processes and they contribute to the pathological developments of various diseases, including autoimmune diseases. To gain the further understanding, we estimate the expression of lncRNAs in primary immune thrombocytopenia (ITP). Methods: In this study, microarray studies were performed to characterize expression profiles of various lncRNAs and mRNAs in blood samples collected from ITP patients. Quantitative real-time PCR (qR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…TNF and granulocyte macrophage colony-stimulating factor signaling were the most interested pathways. Interestingly, lncRNAs ENST00000440492, ENST00000528366, NR_038920, and ENST00000552576 were able to distinguish newly diagnosed from chronic ITP (120). Finally, Peng et al used gene expression profiling analysis and whole-exome sequencing on samples from family members with ITP, sporadic ITP cases and healthy individuals and identified a potential pathologic p.G76S heterozygous mutation on the TNFRSF13B gene.…”
Section: Studies On Inflammatory Cytokinesmentioning
confidence: 99%
“…TNF and granulocyte macrophage colony-stimulating factor signaling were the most interested pathways. Interestingly, lncRNAs ENST00000440492, ENST00000528366, NR_038920, and ENST00000552576 were able to distinguish newly diagnosed from chronic ITP (120). Finally, Peng et al used gene expression profiling analysis and whole-exome sequencing on samples from family members with ITP, sporadic ITP cases and healthy individuals and identified a potential pathologic p.G76S heterozygous mutation on the TNFRSF13B gene.…”
Section: Studies On Inflammatory Cytokinesmentioning
confidence: 99%
“…Over the past few years, it has been reported that lncRNAs are involved in the pathogenesis of ITP [23]. Ayoub et al indicated that lncRNAs metastasis associated in lung denocarcinoma transcript 1 (MALAT1) and THRIL could be potential markers of ITP [24].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia is a common sign of MM [ 64 ]. In the study by Li et al [ 65 ], a relation between autoimmune idiopathic thrombocytopenic purpura and an increased level of lncRNA was described. It is suggested that lncRNAs affect and mediate the functions of the gene network in this disease [ 65 ].…”
Section: Discussionmentioning
confidence: 99%